The Effect of Thesis on Thesis Failure Using Linear Regression - Muhammad Rijal Yahya; Dihin Muriyatmoko; Triana Harmini (JOINCS (Journal of Informatics, Network, and Computer Science), 2021)
The process of writing scientific papers of Informatics Engineering students, determining the title or theme is one of the success and failure factors of students in their thesis. Failure in the thesis in this study means that the thesis that has been completed by students is not used or is not published in the form of a scientific paper. Since January 2018-2020 there have been 40 titles / themes at Darussalam Gontor University published by students. Of the total of all theses, 23 themes experienced failures. The purpose of this research was held to analyze the relationship to thesis failure between themes. This study uses quantitative data research with linear regression data analysis techniques, the independent variable in this study is the thesis theme and the dependent variable in thesis failure. The results of this study indicate that the value of multipleiRi = 0.9938 indicates that the correlation is very strong, while the value ofiR squarei = 0.9876 indicates that the effect of themes is 98.76% on thesis failure, while the remaining 1.24% is influenced by other factors.